Bone-marrow derived cells do not contribute to new beta-cells in the inflamed pancreas - Jiang, Yinan; Wiersch, John; Wu, Wei; Qian, Jieqi; Adama, Maharana Prathap R.; Wu, Nannan; Yang, Weixia; Chen, Congde; Zhu, Lingyan; Prasadan, Krishna; Gittes, George K.; Xiao, Xiangwei (Frontiers in Immunology, 2023)
The contribution of bone-marrow derived cells (BMCs) to a newly formed beta-cell population in adults is controversial. Previous studies have only used models of bone marrow transplantation from sex-mismatched donors (or other models of genetic labeling) into recipient animals that had undergone irradiation. This approach suffers from the significant shortcoming of the off-target effects of irradiation. Partial pancreatic duct ligation (PDL) is a mouse model of acute pancreatitis with a modest increase in beta-cell number. However, the possibility that recruited BMCs in the inflamed pancreas may convert into beta-cells has not been examined. Here, we used an irradiation-free model to track the fate of the BMCs from the donor mice. A ROSA-mTmG red fluorescent mouse was surgically joined to an INS1Cre knock-in mouse by parabiosis to establish a mixed circulation. PDL was then performed in the INS1Cre mice 2 weeks after parabiosis, which was one week after establishment of the stable blood chimera. The contribution of red cells from ROSA-mTmG mice to beta-cells in INS1Cre mouse was evaluated based on red fluorescence, while cell fusion was evaluated by the presence of green fluorescence in beta-cells. We did not detect any red or green insulin+ cells in the INS1Cre mice, suggesting that there was no contribution of BMCs to the newly formed beta-cells, either by direct differentiation, or by cell fusion. Thus, the contribution of BMCs to beta-cells in the inflamed pancreas should be minimal, if any.